Time mapping: charting transcultural and First Nations histories and geographies in doctoral education. Issue 2 (4th March 2021) - Manathunga, Catherine; Qi, Jing; Bunda, Tracey; Singh, Michael
ABSTRACT: In this article, we introduce a time mapping methodology to chart the impact of transcultural and First Nations' histories, geographies and cultural knowledges on doctoral education. Drawing upon a 'Southern', postcolonial-decolonial theoretical framing and extending textual life history methodologies, we argue that time mapping is a visual methodology that has the power to disrupt managerial, auditing discourses that have come to dominate present understandings of doctoral education. We present the time maps of migrant, international candidates and Australian First Nations candidates and supervisors, creating spaces for narratives of migration, war, discrimination, destruction, colonisation, change, survival, faith, energy, language and cultural revival, growth, inspiration and the power of Country. We seek to re-humanise discourses about doctoral education.